Intrinsic and Extrinsic Motivation for Elementary Teachers: Saudi Arabian Context - Mahdi Albishi (Canadian Society for Studies in Education, 2021)
This paper describes factors that intrinsically and extrinsically motivate elementary teachers in an all-boys elementary school in Saudi Arabia. Using a qualitative case study research methodology, data were collected via 14 semi-structured individual interviews, two focus group interviews, and a month of classroom observations of Grades 4, 5, and 6 teachers. Using an inductive approach, the data were analyzed using thematic analysis. The analysis was conducted in five phases: transcription of interviews in Arabic, transcript translation from Arabic to English, data analysis for emerging themes, and triangulation of the data from the interviews, focus groups and classroom observations. The findings revealed Saudi Arabian teachers were motivated intrinsically through (a) their religious beliefs associated with teachers, (b) social connection with colleagues and students, and (c) their pride when witnessing the students' academic achievement. Extrinsic motivations were (a) awards and rewards, (b) salary and tenure, and (c) proximity to family. Analyzing the findings using self-determination theory (SDT), the intrinsic motivation was based on their psychological needs, and extrinsic motivation was linked to commitment to their profession. The study concludes with a call for the Saudi education system to use educational research to inform policies, such as creating professional development opportunities, which further lends to teacher motivations.